Anti-Inflammatory Effect of Curcumin on the Mouse Model of Myocardial Infarction through Regulating Macrophage Polarization. (21st August 2021) - Yan, Shaoxi; Zhou, Mo; Zheng, Xiaoyun; Xing, Yuanyuan; Dong, Juan; Yan, Mengwen; Li, Rui
Abstract : Inflammation causes tissue damage and promotes ventricular remodeling after myocardial infarction (MI), and the infiltration and polarization of macrophages play an important role in regulating inflammation post-MI. Here, we investigated the anti-inflammatory function of curcumin after MI and studied its relationship with macrophage polarization. In vivo, curcumin not only attenuated ventricular remodeling 3 months after MI but also suppressed inflammation during the first 7 days post-MI. Importantly, the results of qPCR and immunochemistry showed that curcumin decreased M1 (iNOS, CCL2, and CD86) but increased M2 macrophage (Arg1, CD163, and CD206) marker expression in the myocardium of MI mice during the first 7 days post-MI. And flow cytometry analysis indicated that curcumin suppressed M1 (CD45+Gr-1-CD11b+iNOS+ cells) but enhanced M2 macrophage (CD45+Gr-1-CD11b+Arg+ cells) expansion in the myocardium of MI mice during the first 7 days post-MI. In vitro, curcumin decreased LPS/IFN γ -elevated M1 macrophage marker (iNOS and CD86) expression and the proportion of M1 macrophages (iNOS+F4/80+ cells) but increased LPS/IFN γ -suppressed M2 macrophage marker (Arg1 and CD206) expression and the proportion of M2 macrophages (Arg1+F4/80+ cells). In addition, curcumin modulates M1/M2 macrophage polarization partly via AMPK. In conclusion, curcumin suppressed the MI-induced inflammation by modulating macrophage polarization partly via the AMPK pathway.